Potential ecological effects of wind farm location on the example of the Małopolska region in Poland - Blazy, Rafał; Łabuz, Rita (Frontiers in Energy Research, 2025)
Environmental challenges, such as climate change and resource depletion, are driving the search for alternative energy sources like wind energy. This study explores the ecological effects of installing wind turbines in Małopolska, Poland. The goals are to find suitable wind power locations, analyse the impact of distance-to-building criteria, and assess carbon emission reduction. The study was carried out in two stages: identification of possible sites for wind farms, taking into account the two criteria of distance from residential buildings of 700 m and 500 m, and estimation of potential carbon emission reductions. Results show optimal locations in north and south of Małopolska. Reducing the distance criteria doubles suitable areas, potentially decreasing Poland’s annual carbon emissions by 0.44%–1.03% and generating up to 1.49 TWh of wind energy, comparable to combined heat and power (CHP) plants in the region.